Toxoplasma Encephalitis in Atypical Hosts at an Academic Cancer Center. (30th March 2016) - Morjaria, Sejal; Epstein, David J.; Romero, Fabian A.; Taur, Ying; Seo, Susan K.; Papanicolaou, Genovefa A.; Hatzoglou, Vaios; Rosenblum, Marc; Perales, Miguel-Angel; Scordo, Michael; Kaltsas, Anna
Abstract: Toxoplasma encephalitis is a well recognized complication of acquired immune deficiency syndrome, solid organ transplantation, and allogeneic hematopoietic stem cell transplantation (HSCT). However, patients with hematologic malignancies not treated with allogeneic HSCT may also develop this condition, which requires high clinical suspicion and consideration for prophylactic therapy.